The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1677/joe-06-0002
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of sphingomyelin synthase 2 in the seminiferous epithelium of adult rat testes

Abstract: Sphingomyelin synthase 2 (SMS2) is an enzyme that catalyzes the conversion of phosphatidylcholine and ceramide to sphingomyelin and diacylglycerol, and it is crucial to cellular lipid metabolism. Using the technique of subtraction hybridization, we have isolated a full-length cDNA encoding SMS2 from rat testes, which shared 93 and 87% identity at the nucleotide level with SMS2 in mice and humans respectively. A specific polyclonal antibody was prepared against a 20 amino acid peptide of NH 2 -FSWPLSWPPGCFKSSCK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The human genome contains two of these genes, named SMS1 and SMS2. The corresponding enzymes fulfill essentially all criteria attributed previously to SM synthase and reside in organelles where SM synthesis is known to occur, namely the Golgi (SMS1) and plasma membrane (SMS2) (15,17). In line with these findings, Yamaoka et al (4) reported the expression cloning of human SMS1 using a mouse lymphoid cell line with severely reduced SM synthase activity and susceptibility to methyl-␤-cyclodextrin-induced cell death.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The human genome contains two of these genes, named SMS1 and SMS2. The corresponding enzymes fulfill essentially all criteria attributed previously to SM synthase and reside in organelles where SM synthesis is known to occur, namely the Golgi (SMS1) and plasma membrane (SMS2) (15,17). In line with these findings, Yamaoka et al (4) reported the expression cloning of human SMS1 using a mouse lymphoid cell line with severely reduced SM synthase activity and susceptibility to methyl-␤-cyclodextrin-induced cell death.…”
mentioning
confidence: 63%
“…Together with the finding that SMS2 primarily resides at the plasma membrane, these observations indicate that SMS2 operates as the major if not only cell surface-associated SM synthase in HeLa cells. Because SMS2 is expressed in essentially all major tissues (15,17,36) and in a variety of mammalian cell lines (this study), we anticipate that the presence of a cell surface-associated SM synthase activity is a general feature of mammalian cells.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with our observation, studies of SMS2 function in sperm cell also suggest that SMS2 is important for reconstruction of plasma membrane structure. 30 SMS2 deficiency could alter signal transduction mediated by lipid raft-associated receptors. As reported, the interaction of SM and cholesterol drives the formation of plasma membrane rafts, 5 and the relative proportions of both SM and cholesterol appear critical for the stability and function of lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…In the seminiferous epithelium of rat testis, stage-specifi c expression of a form of SMS2 was localized to late round spermatids and early elongating spermatids and not present in late elongated spermatids or Sertoli cells ( 39 ). This enzyme was suggested to play a role in acrosome formation and the plasma membrane restructuring that occurs between late round spermatids and early elongating spermatids.…”
Section: Germ Cell-neutral Lipidsmentioning
confidence: 99%